Endometriosis in adolescence: Early manifestation of the traditional disease or a unique variant?. (April 2020) - Tsonis, O.; Barmpalia, Z.; Gkrozou, F.; Chandraharan, E.; Pandey, S.; Siafaka, V.; Paschopoulos, M.
Abstract: Little is known about Endometriosis in Adolescents and its prevalence is yet to be estimated. Traditional Endometriosis seems to be, by far, quite different with this unique variant when it comes to clinical presentation, management and course of the disease. Further research needs to be conducted in order to classify these two, phenomenically similar, diseases. Adolescents with a history of dysmenorrhea and chronic pelvic pain (CPP) imply findings suggestive of endometriosis. The severity of the disease is variable, from superficial endometriosis to deep endometriotic lesions or even ovarian endometriomas. The course of the disease also suggests the necessity of a more personalized approach since among adolescents, endometriosis could resolve or even aggravate with no particular pathophysiological pattern. Some studies suggest that appropriate treatment should be based on the understanding of the pathophysiologic mechanisms. Long term course of the disease, as well as, a high recurrence rate pose a difficulty to scientists, deciding conservative over operative surgery. Some believe that early operation on superficial forms of endometriosis could potentially prevent deep endometriotic lesions in the long-run. Others find medication such as, combined oral contraceptive pills (COCPs), progestins, levonorgestrel intrauterine device or gonadotrophin releasing hormone analogues (GnRHa), more appropriate for this age group. Last but not least, operation with post-operative hormonal treatment remains the most common treatment approach. Nevertheless, our limited understanding of the disease, as well as, particular factors needed to be taken into consideration, for instance, bone formation in this age group, underline the necessity of further studies, needed to be appointed, in order to determine the best diagnostic and therapeutic approach.